Improved determination of the width of the top quark - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Aoki, M.; Askew, A.; Åsman, B.; et al. (American Physical Society (APS), 2012)
We present an improved determination of the total width of the top quark, Γ t, using 5.4fb -1 of integrated luminosity collected by the D0 Collaboration at the Tevatron pp̄ Collider. The total width Γ t is extracted from the partial decay width Γ(t→Wb) and the branching fraction B(t→Wb). Γ(t→Wb) is obtained from the t-channel single top-quark production cross section and B(t→Wb) is measured in tt̄ events. For a top mass of 172.5 GeV, the resulting width is Γ t=2.00-0.43+0.47GeV. This translates to a top-quark lifetime of τ t=(3.29-0.63+0.90)×10 -25s. We also extract an improved direct limit on the Cabibbo-Kobayashi-Maskawa quark-mixing matrix element 0.81<|V tb|≤1 at 95% C.L. and a limit of |V tb′|<0.59 for a high-mass fourth-generation bottom quark assuming unitarity of the fourth-generation quark-mixing matrix. © 2012 American Physical Society.